Nonlinearity, Bifurcation and Chaos : Theory and Applications - Awrejcewicz, Jan; Hagedorn, Peter; Awrejcewicz, Jan; Hagedorn, Peter (IntechOpen, 2012)
Nonlinearity, Bifurcation and Chaos - Theory and Application is an edited book focused on introducing both theoretical and application oriented approaches in science and engineering. It contains 12 chapters, and is recommended for university teachers, scientists, researchers, engineers, as well as graduate and post-graduate students either working or interested in the field of nonlinearity, bifurcation and chaos.
English
Keywords: Differential calculus & equations; Differential calculus & equations